2015
DOI: 10.1007/s00404-015-3701-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors affecting cervical adenocarcinoma: 10 years experience in a single institution

Abstract: Although in our country incidence of adenocarcinoma is lower than the ones reported in western countries, in general our results are consistent with those reported in the literature. Better outcomes are observed in both early stages and young patients. Also, we found that FIGO stage, grade and lymph node metastases to be significant prognostic factors for survival in cervical adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…As well as histologic type, several factors, including age, FIGO stage, tumor size, stromal invasion, lympho-vascular space invasion (LVSI), parametrial involvement, and the use of concurrent chemotherapy, have been identified in previous studies on cervical carcinoma and incorporated into prediction models (12,(23)(24)(25). In our study with UAC, the following were identified as independent prognostic factors and subsequently incorporated into the model: tumor grade, stage T, stage N, stage M, size of the tumor, and surgery of the primary site, which was consistent with the findings of other studies (7)(8)(9)27). In the nomogram, stage T made the largest contribution to prognosis, followed by tumor size and tumor grade.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As well as histologic type, several factors, including age, FIGO stage, tumor size, stromal invasion, lympho-vascular space invasion (LVSI), parametrial involvement, and the use of concurrent chemotherapy, have been identified in previous studies on cervical carcinoma and incorporated into prediction models (12,(23)(24)(25). In our study with UAC, the following were identified as independent prognostic factors and subsequently incorporated into the model: tumor grade, stage T, stage N, stage M, size of the tumor, and surgery of the primary site, which was consistent with the findings of other studies (7)(8)(9)27). In the nomogram, stage T made the largest contribution to prognosis, followed by tumor size and tumor grade.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, it is necessary to develop an individualized predictive model that supplements the FIGO staging system for predicting prognosis and optimizing treatment strategies in UAC. However, due to its relatively low incidence, few studies on UAC have focused on the prediction of patient prognosis or treatment outcomes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Baalbergen et al [1] found lymph node metastases was a prognostic factor in AC. Khalil et al [18] found that 5-year survival rate was significantly worse in patients with lymph node metastasis (81% vs 20%). But in our study, lymph node metastasis was not a prognostic factor for stage IB cervical AC.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate for those age <50 years and those age >50 years was 81% and 54%. Khalil et al [18] found that age was a significant prognostic factor by univariate analysis. However, in our study, age was not a prognostic factor in univariate or multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation